Design of a robust controller for DC/DC converter–electrolyzer systems supplied by μWECSs subject to highly fluctuating wind speed. (May 2020) - Alonge, Francesco; Collura, Stefania Maria; D'Ippolito, Filippo; Guilbert, Damien; Luna, Massimiliano; Vitale, Gianpaolo
Abstract: A buck-based, isolated, high-voltage-ratio DC/DC converter that allows supplying a proton exchange membrane (PEM) electrolyzer from a micro-wind energy conversion system ( μ WECS) has been recently presented. It exhibits low ripple at the switching frequency on the output voltage and current and represents an attractive solution for low-cost hydrogen production. In this paper, a more accurate mathematical model of such a converter is derived and discussed. Then, a model-based robust controller is designed in the frequency domain using the Internal Model Control structure and in the context of H 2 ∕ H ∞ optimal control. The controller satisfies the condition of robust stability and behavior, i.e., it guarantees stability and the desired behavior in the presence of parametric variations and unmodeled dynamics. In particular, the robustness in the presence of variations of DC-link voltage and buck input inductance is verified from the theoretical point of view. The validation of the controller is performed by integrating it into a detailed switching model of the DC/DC converter, which is implemented on a widely used circuit-oriented simulator. Good results are obtained in terms of dynamic and steady-state behavior, even in the presence of the above variations. A comparison is also carried out with the results obtained using an integral controller designed on the basis of the above mathematical model. Such a comparison shows the superiority of the robust controller over the integral controller in all the operating conditions, especially when the DC-link voltage is subject to significant variations and is affected by a non-negligible low-frequency ripple due to the presence of the diode rectifier at the output of the μ WECS.